Analisis Pengaruh Positioning Daya Tarik Wisata Terhadap Keputusan Wisatawan Untuk Berkunjung Di Objek Wisata Kebun Raya Unmul Samarinda - Rinto Dwiatmojo; Isransyah Nur (EDUTOURISM Journal Of Tourism Research, 2019)
This study aims to determine whether the positioning variable has a partial and simultaneous influence on tourists' decision to visit the Samarinda Unmul Botanical Garden? Which is the most dominant influence on the decision of tourists visiting the Botanical Gardens Unmul Samarinda? This study uses a Multiple Regression analysis to analyze research results. Ha accepted that there is an influence between the experimental concept on tourists' decision to visit. Thi's evidenced by the value of tcount> t table (3.049> 1.661), the significance is less than 0.05 (0.003).